Proofs

A proof is a series of claims that lead to a conclusion. Some proofs are conditional, which means that the claims can only be made under certain conditions. Click on a statement to see the proof

Subtract Number 3
if 180 + (90 ⋅ (-1)) = y, then 90 = y

Add Number to Both Sides
if a + 90 = 180, then a = 90

Add Number to Both Sides 2
if 90 + a = 180, then a = 90

Add Number to Both Sides 3
if 180 = 90 + a, then a = 90

Divide 180 by 2
if a = 180 ⋅ (1 / 2), then a = 90

Add Two 90
if the following are true:
  • a = 90
  • b = 90

then a + b = 180


Substitute 6
if the following are true:
  • a = ((b + c) + d) + e
  • d + e = f

then a = (b + c) + f


Substitute 7
if the following are true:
  • a + (b ⋅ (-1)) = c
  • b = d

then a + (d ⋅ (-1)) = c


Add Term to Both Sides 7
if a + b = c, then b = c + (a ⋅ (-1))

Substitution 8
if the following are true:
  • a + b = c
  • a = d

then d + b = c


Substitute 9
if the following are true:
  • a + b = c
  • d = a

then d + b = c


Substitution Example 10
if the following are true:
  • a + b = c
  • b = d

then a + d = c


Substitute 2
if the following are true:
  • a + b = c
  • d = b

then a + d = c


Add Term to Both Sides 6
if a + b = c, then a = c + (b ⋅ (-1))

Add Term to Both Sides 5
if a + b = c, then b = c + (a ⋅ (-1))

Subtract Equation
if a + b = c, then a = c - b

Subtract Equation 2
if a + b = c, then b = c - a

Substitute First Term
if the following are true:
  • (a + b) + c = d
  • a = e

then (e + b) + c = d


Add Term to Both Sides 4
if (a + b) + c = d, then b + c = d + (a ⋅ (-1))

Substitution 16
if a + b = c, then ((x + a) + b) + y = (x + c) + y

Sum Equation
if (a + b) + c = d, then a + c = d - b

Divide Both
if the following are true:
  • a / b = c / d
  • d = e

then a / b = c / e


Divide Substitute
if the following are true:
  • a = b / c
  • b = d

then a = d / c


Divide Substitute 2
if the following are true:
  • a = x
  • b = y

then a / b = x / y


Divide New
if the following are true:
  • a / b = c
  • d = a

then c = d / b


Divide New B
if the following are true:
  • c = a / b
  • d = a

then c = d / b


Divide New 2
if the following are true:
  • a / b = c
  • d = a

then d / b = c


Divide Substitute 4
if the following are true:
  • a = w
  • b = x
  • c = y
  • d = z

then (a - b) / (c - d) = (w - x) / (y - z)


Whole is Greater Than Parts
if the following are true:
  • a = b + c
  • b > 0

then a > c


Slope 1
if the following are true:
  • f = (a - b) / (c - d)
  • a = w
  • b = x
  • c = y
  • d = z

then f = (w - x) / (y - z)


Associative
a + (b + c) = (a + b) + c

Zero Plus a
0 + a = a

Subtract Commutative
(a ⋅ (-1)) + a = 0

Subtract Commutative 2
((-1) ⋅ a) + a = 0

Subtraction Example
a + (b ⋅ (-1)) = a - b

Subtract to Zero
a - a = 0

Subtract Zero Example
a - 0 = a

Subtract Associative
(a + b) - c = a + (b - c)

Subtract 1
(b + a) - a = b

Multiplicative Identity 2
a = a1

Multiplicative Identity 3
1a = a

Distributive Property Variation 2
(b + c) ⋅ a = (ab) + (ac)

Distributive Property Variation 3
(a + b) ⋅ c = (ac) + (bc)

Distributive Property Variation
(ab) + (ac) = a ⋅ (b + c)

Distributive Property 5
(ac) + (bc) = (a + b) ⋅ c

Division Theorem
a ⋅ (1 / b) = a / b

Division is Commutative
a ⋅ (b / c) = (ab) / c

Associative Property
(ab) / c = a ⋅ (b / c)

Associative Property of Multiplication 2
a ⋅ (bc) = (ab) ⋅ c

Swap Terms 2 and 3
(ab) ⋅ c = (ac) ⋅ b

Multiply Reorder 2
(ab) ⋅ c = (bc) ⋅ a

Distribute Subtract
(a - b) ⋅ c = (ac) - (bc)

Add Associative
((a + b) + c) + d = a + ((b + c) + d)

Add Associative 2
(a + b) + c = (a + c) + b

Rearrange Sum Equal 2
(a + b) + c = (b + a) + c

Rearrange Sum Equal 3
(a + b) + c = (c + a) + b

Rearrange Sum Equal 4
(c + a) + b = (a + b) + c

Subtract Reorder
(a + b) - c = (a - c) + b

Add 6 Numbers
((a + b) + c) + ((d + e) + f) = ((((a + b) + c) + d) + e) + f

Rearrange Sum 6
((((a + b) + c) + d) + e) + f = ((((a + e) + b) + d) + f) + c

Rearrange Sum 6 2
((((a + b) + c) + d) + e) + f = ((a + b) + (c + d)) + (e + f)

Zero Plus a Plus B
(0 + a) + b = a + b

Swap B And C
((a + b) + c) + d = ((a + c) + b) + d

Manipulation 2
(a ⋅ (b ⋅ (-1))) ⋅ 2 = (ab) ⋅ (-2)

Manipulation 3
(a ⋅ (-1)) ⋅ (a ⋅ (-1)) = aa

Distribute Half
(a ⋅ (1 / 2)) + (a ⋅ (1 / 2)) = a

Doubling a Number
a + a = a2

Add Three
(a + a) + a = a3

Add Four
((a + a) + a) + a = a4

Multiply 2
((a + b) + a) + b = (a + b) ⋅ 2

Sum Squared Theorem
(a + b) ⋅ (a + b) = ((aa) + ((ab) ⋅ 2)) + (bb)

Divide Simplify
if not (b = 0), then (bd) ⋅ (a / b) = da

Divide Simplify 2
if not (d = 0), then (bd) ⋅ (c / d) = bc

Simplify
(0 + (a2)) / 2 = a

Simplify 2
if not (2 = 0), then (a2) ⋅ (1 / 2) = a

Simplify 3
if not (2 = 0), then ((b2) + (a2)) / 2 = b + a

Multiply by 0
0a = 0

Inverse Product Theorem
if not (a = 0), then (1 / a) ⋅ a = 1

Reordering Terms Theorem
(ab) ⋅ c = (ca) ⋅ b

Multiply By 1 Theorem
if not (c = 0), then (b / c) ⋅ c = b

Multiply by 1 3
if a1 = b, then a = b

Multiply Both Sides 2
if the following are true:
  • a = b / c
  • not (c = 0)

then ca = b


Double
if a + a = b, then a2 = b

Subtract Substitute 2 Vars
if the following are true:
  • a = b
  • c = d

then a - c = b - d


Multiply by 2
if the following are true:
  • a2 = b
  • not (2 = 0)

then a = b ⋅ (1 / 2)


Double to Half
if the following are true:
  • a + a = b
  • not (2 = 0)

then a = b ⋅ (1 / 2)


Rearrange Sum
if (a + b) + c = d, then (a + c) + b = d

Rearrange Sum 2
if (a + b) + c = d, then (b + a) + c = d

Simplify Rearrange Sum 6
if the following are true:
  • x = c + d
  • y = e + f

then ((a + b) + (c + d)) + (e + f) = ((a + b) + x) + y


Divide Each Side
if the following are true:
  • ab = c
  • not (b = 0)

then a = c / b


One Eighty 3
if (a + b) + b = 180, then a + (b2) = 180

Transitive
if x = (0 + (a2)) / 2, then x = a

Transitive 2
if the following are true:
  • x = ((b2) + (a2)) / 2
  • not (2 = 0)

then x = b + a


Subtract Zero Example 2
if f = a - 0, then f = a

Transitive Subtract 3
if f = (a + b) - b, then f = a

Transitive Inequality
if the following are true:
  • a < b
  • c = a

then c < b


Subtract Substitute
if a = b, then x - a = x - b

Substitute 11
if the following are true:
  • a = b
  • f = c - a

then f = c - b


Subtract Both Sides 3
if a = b, then a - c = b - c

Subtract Move Over
if a - b = c, then a = c + b


Pages: 190 191 192 ... 193